High BLM Expression Predicts Poor Clinical Outcome and Contributes to Malignant Progression in Human Cholangiocarcinoma - Du, Xiaolong; Zhang, Chen; Yin, Chuanzheng; Wang, Wenjie; Yan, Xueke; Xie, Dawei; Zheng, Xichuan; Zheng, Qichang; Li, Min; Song, Zifang (Frontiers in Oncology, 2021)
The molecular mechanism underlying the tumorigenesis of the highly malignant cancer - cholangiocarcinoma (CCA) is still obscure. In our study, CCA expression profile data were acquired from The Cancer Genome Atlas (TCGA) database, and differentially expressed genes in the TCGA-CHOL dataset were utilized to construct a co-expression network via WGCNA. The blue gene module associated with the histopathologic grade of CCA was screened. Then, 5 candidate hub genes were screened by combining the co-expression network with PPI network. After progression and survival analyses, BLM was ultimately identified as the real hub gene. Moreover, the ROC curve analysis suggested that BLM had favorable diagnostic and predictive recurrence value for CCA. The GSEA results for a single hub gene revealed the importance of cell cycle-related pathways in CCA progression and prognosis. Furthermore, we detected BLM expression in vitro, and the results demonstrated that the expression level of BLM was much higher in CCA tissues and cells relative to adjacent non-tumor samples and normal bile duct epithelial cells. Additionally, after further silencing BLM expression by siRNA, the proliferation and migration ability of cholangiocarcinoma cells were all inhibited, and the cell cycle was arrested. Altogether, a real hub gene (BLM) and cell cycle-related pathways were identified in the present study, and BLM may be involved in CCA progression and could act as a reliable biomarker for potential diagnosis and prognostic evaluation.